Illusions of Learning: Irrelevant Emotions Inflate Judgments of Learning. (10th September 2014) - Baumeister, Roy F.; Alquist, Jessica L.; Vohs, Kathleen D.
Abstract People use assessments of how much they have learned to choose and recommend instructors, seminars, and weekend trips. How do people assess how much they have learned? Recent theorizing has depicted emotion as a cue for learning, and so people may be misled by recent emotional states to infer that they have learned more than they actually have. Four studies showed that people associated emotion with learning and believed, often falsely, that they learned more when in an emotional than unemotional state. Factual lessons were coupled with manipulations of arbitrary, irrelevant emotional states. Participants rated that they learned more after an emotion had been induced than in emotionally neutral control conditions. These differences remained significant after controlling for actual learning as measured by objective tests, which was unaffected by emotion. This illusion of learning caused by emotion was robust with respect to changes of procedure and sample, including whether the emotion came before or after the information to be learned. Alternative explanations were ruled out, including that emotion would intensify ratings generally, that emotion would make incoming information seem particularly personally relevant, that emotion increased engagement in the research, and that illusory learning would depend on retrospective exaggeration of one's prior ignorance. Because irrelevant emotions can increase people's judgments that they have learned something, incidental emotional experiences could increase a person's likelihood of deciding to take another class with a particular instructor, to sign up for another leadership seminar, or to engage in a risky (but emotion‐filled) excursion. Copyright © 2014 John Wiley & Sons, Ltd.